ANALISIS PREDIKSI FINANCIAL DISTRESS DENGAN METODE ALTMAN (Z-SCORE), SPRINGATE (S-SCORE), DAN ZMIJEWSKI (X-SCORE) PADA PERUSAHAAN TAKSI KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Luthfiyana Adfanin; Siti Aisyah Hidayati; I Nyoman Nugraha Ardana Putra (Master of Management, Mataram University, 2023)
This study aims to prediction analysis financial distress using the Altman (Z-Score), Springate (S-Score), and Zmijewski (X-Score) methods for Conventional Taxi Companies Listed on the Indonesia Stock Exchange based on the company's annual financial reports for the 2019-2021 period. The type of research used in this research is descriptive research with a quantitative approach. The data used in this study are the financial statements of conventional taxi companies for the 2019-2021 period published in the website Indonesia stock exchange. The results showed that the Altman Method (Z-Score), PT. Express Transindo Utama Tbk for the 2019-2021 period is predicted Financial Distress and PT. Blue Bird Tbk predicts the 2019-2021 period Non Financial Distress. On the Springate method (S-Score), PT. Express Transindo Utama Tbk 2019 and 2020 are predicted Financial Distress and 2021 predicted Non Financial Distress, then PT. Blue Bird Tbk predicts the 2019-2021 period Financial Distress. At method Zmijewski (X-Score), PT. Express Transindo Utama Tb. 2019 and 2020 are predicted Financial Distress and 2021 predicted Non Financial Distress, then PT. Blue Bird Tbk predicts the 2019-2021 period Non Financial Distress.